Simultaneous determination of standardized ileal digestible tryptophan and lysine for barrows from 15 to 30 kg live weight - Pasquetti, T. J.; Pozza, P. C.; Moreira, I.; Santos, T. C.; Diaz-Huepa, L. M.; Castilha, L. D.; Perondi, D. [UNESP]; Carvalho, P. L. O.; Kim, S. W. (Elsevier B.V., 2015)
The digestible amino acid (AA) determination of ingredients, or experimental diets, are essential in obtaining the real levels of AA that are being studied, as well as of other indispensable AA, because the lack of a single indispensable AA may limit pig growth performance. Two experiments were conducted to determine the optimum levels and the ideal ratio of standardized ileal digestible (SID) Trp and Lys for barrows from 15 to 30 kg of live weight. The first experiment (Exp. 1) was conducted to determine the SID AA content of the basal diet used in the growth performance study (Exp. 2). Ten crossbred barrows (21.5 +/- 1.6 kg live weight) were used in Exp. 1. Pigs were fed a basal diet and a protein free diet to determine the SID of Trp, Lys, and all other indispensable AA of the basal diet. In Exp. 2, 64 barrows (15.0 +/- 1.6 kg) were allotted to 16 diets in a 4 x 4 factorial arrangement of treatments (1.55, 1.85, 2.15, and 2.45 g SID Trp and 9.72, 11.12, 12.52, and 13.92 g SID Lys/kg) with 4 replications per treatment In both Exp. 1 and 2, each pig was considered as an experimental unit. Growth performance, Longissimus muscle (LM), backfat thickness, and plasma urea nitrogen (PUN) were evaluated. Average daily feed intake and average daily gain increased linearly (P < 0.05) with increasing levels of SID Trp. There was a quadratic effect (P=0.04) of dietary SID Trp and Lys levels on the gain:feed, and the optimal levels were estimated to be 2.1 (0.65 g/Mcal ME) and 11.98 g/kg (3.71 g/Mcal ME), respectively, resulting in a SID Trp:Lys of 17.5:100. A quadratic effect of SID Trp (P=0.021) and Lys (P=0.026) levels on LM was observed, and the optimum levels were 2.08 and 11.36 g/kg diet, respectively, with a Trp:Lys of 183:100. The amount of PUN decreased linearly (P=0.004) as SID Lys increased. For pigs used in our study (between 15 and 30 kg live weight), the SID Trp and SID Lys requirements are 2.10 and 11.98 g/kg, respectively. The corresponding Trp:Lys are 17.5:100. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Lysine; Pigs; Response surface; Requirements; Standardized ileal amino acid digestibility; Tryptophan